Predictive Utility of the HALP and Modified HALP Score for the Assessment of Operative Complications in Patients Undergoing Laparoscopic Cholecystectomy for Acute Cholecystitis - Yasemin Keskin; Hakan Sevinç; Selçuk Mevlüt Hazinedaroğlu; Şevket Barış Morkavuk; Şiyar Ersöz (Diagnostics)
Background and Objectives: The aim of the present study was to calculate HALP and modified HALP scores for patients diagnosed with acute cholecystitis (AC) and to determine the predictive utility of these scores for surgical timing and morbidity in patients who underwent surgery for AC. Materials and Methods: This study included data from 641 patients who underwent surgery for AC between January 2010 and May 2023. The HALP score was calculated using the formula hemoglobin (g/L) × albumin (g/L) × lymphocyte (109/L)/platelets (109/L). The modified HALP score was calculated using the formula hemoglobin (g/L) × albumin (g/L) × lymphocyte (109/L) × platelets (109/L). Results: The mean HALP score was 46.81, and the mean modified HALP score was 2,758,401.21. Laparoscopic cholecystectomy (LC) was successfully completed in 582 (90.8%) patients. When examining the relationship between HALP and modified HALP scores and the procedure type, a statistically significant difference was found in the distribution of median HALP and modified HALP scores between the LC and laparoscopic and open cholecystectomy (LTOC) groups. For patients with a HALP score < 34.43 and modified HALP score < 2,077,019, the likelihood of conversion to open surgery increased, with a sensitivity of 65.5% vs. 58.8% and a specificity of 66.1% vs. 59.3%. In patients who underwent surgery, there was a significant difference in the LTOC between the HALP score and modified HALP score cut-off groups (p < 0.001 and, p = 0.007). Conclusions: Evaluation of the HALP score is a promising and valuable assessment method for designing appropriate treatment and management strategies for patients with AC.